2010
DOI: 10.1021/ol902894p
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of α-Ketoamides via 2-Acyl-5-aminooxazoles by Reacting Acyl Chlorides and α-Isocyanoacetamides

Abstract: Acyl chlorides and alpha-isocyanoacetamides undergo an efficient reaction in dichloromethane in the presence of triethylamine to give 2-acyl-5-aminooxazoles. Subsequent acid hydrolysis of the 5-aminooxazole moiety leads to alpha-ketoamides in good overall yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…1 pharmaceuticals (rapamycin, enzyme inhibitors) and agrochemicals (FK506). 2-4 α-Ketoamides are synthesized from diverse substrates such as methyl-ketones, 5-10 aldehydes/arylglyox-als, [11][12][13][14][15][16] -ketoacids, [17][18][19][20] terminal alkynes, [21][22][23][24] cyanamides, 25 carbamoyl stannane/ silane with acid chlorides, [26][27][28] addition of aroyl to aryl-acetamides, 29 2,2-dibromo-1-aryl ethanones 30 and double carbonylation of aryl iodides. [31][32][33] Usually in these oxidative amidation, a co-oxidant is required.…”
Section: Tetrahedron Lettersmentioning
confidence: 99%
“…1 pharmaceuticals (rapamycin, enzyme inhibitors) and agrochemicals (FK506). 2-4 α-Ketoamides are synthesized from diverse substrates such as methyl-ketones, 5-10 aldehydes/arylglyox-als, [11][12][13][14][15][16] -ketoacids, [17][18][19][20] terminal alkynes, [21][22][23][24] cyanamides, 25 carbamoyl stannane/ silane with acid chlorides, [26][27][28] addition of aroyl to aryl-acetamides, 29 2,2-dibromo-1-aryl ethanones 30 and double carbonylation of aryl iodides. [31][32][33] Usually in these oxidative amidation, a co-oxidant is required.…”
Section: Tetrahedron Lettersmentioning
confidence: 99%
“…Primarily, there are several routes to their synthesis, for example, palladium‐catalysed double carboxylative amidation of aryl halides, nitrosocarbonyl‐Henry‐denitration cascade, copper catalysed C(α)‐C(β) bond cleavage of saturated aryl ketones, copper catalysed C=C bond cleavage of enaminones, oxidation of amides, reaction of acyl chlorides with α‐isocyanoacetamides, palladium‐catalysed fragmentation of N ‐aryl peptides and silver‐catalysed coupling of benzoylformic acids with tertiary amines …”
Section: Introductionmentioning
confidence: 99%
“…[3] Besides that, Nature has also enveloped α-ketoamides nuclei in several forms. [4] Primarily, there are several routes to their synthesis, [5] for example, palladium-catalysed double carboxylative amidation of aryl halides, [6] nitrosocarbonyl-Henry-denitration cascade, [7] copper catalysed C(α)-C(β) bond cleavage of saturated aryl ketones, [8] copper catalysed C=C bond cleavage of enaminones, [9] oxidation of amides, [10] reaction of acyl chlorides with α-isocyanoacetamides, [11] palladium-catalysed fragmentation of N-aryl peptides [12] and silver-catalysed coupling of benzoylformic acids with tertiary amines. [13] More recently, there have been successful examples of exploiting simultaneous activation of CÀ H and NÀ H bonds to access α-ketoamides.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from this report, the reaction of ketenes with isocyanides and carboxylic acids has not been investigated further, probably due to the very limited number of stable ketenes available. Recently Pirali et al have reported the reaction of acyl chlorides with α-isocyanoacetamides, leading to 2-acyl-5-aminooxazoles [ 5 ]; according to the postulated mechanism the ketene generated in situ from the acyl chloride in the presence of triethylamine reacts first with the isocyanide to form an acylnitrilium ion similar to 6 , that is subsequently trapped intramolecularly by the amidic oxigen to form the final oxazole.…”
Section: Introductionmentioning
confidence: 99%